Telepoint-povećanje pokretljivosti telefonskih aparata bez vrpce - Miroslav Mikula (Promet - Traffic&Transportation, 1970)
This paper deals with major technical and utilization properties of the new system of wireless telephone communication - the TELEPO/NT. The system introduces a modified tapeless telephone technique of increase range and thus the increased mobility of the parties.